The Effect of Education, Income on Economic Growth of Sukabumi Regency - Abdul Aziz Assayuti (West Science Interdisciplinary Studies, 2023)
This study explores the relationship between education, income, and economic growth in Sukabumi Regency, a district in Indonesia. A mixed method approach was used, including a survey of 300 respondents and interviews with interviewees. The survey results show that higher levels of education and income are associated with greater involvement in economic activity and perceptions of economic growth. Interviews revealed several factors influencing this relationship, including government policies, the business environment, and social and cultural attitudes toward education and employment. This study shows that there is a need for targeted and effective policies to encourage education and income growth, as well as broader social and cultural changes to support economic growth in Sukabumi District.